Upaya Penataan PKl Diperkotaan: Studi Kasus di Jalan Kaliurang - Author: Suparwoko (Universitas Islam Indonesia, 2006)
On one hand the existence street vendors (PKL) have a positive impact on its economic contribution including ernployment and economic income of lower people in urban areas. On the other hand, the existence of the streets vendors in urban areas has been blamed because they are making some problems of urban traffic jams and the beautification of cities. As a matter of the fact, they are needed by many people living in urban areas because they can provide cheap goods and services. The paper is to examine the location and place where street vendors are trading during the day and night. The growth of street vendors along the Jalan Kaliurang is due to the potential public facility established along the jalan Kaliurang such as campus, housing, and commercial facilities. The research suggests it is possible to integrate the street vendors as informal sector exist together with forrnal sector in certain areas. The other alternative of street vendor arrangement is that they can possibly working together with any commercial facility along jalan Kaliurang by using its parking area during the night where some of the commercial facilities do not operate in the night.